Increasing the role of zakat institutions in poverty reduction through productive zakat programs in Indonesia. - Sutrisno, Sutrisno; Haron, Razali (2020)
Purpose of the study: The aim of this study is to identify zakat programs that have been implemented by zakat institutions in the context of increasing social roles, especially to reduce poverty. This study concludes that a strategic program in the distribution of zakat to help the poor improve their welfare. Methodology: This study adopts a document analysis approach involving a series of systematic steps to review the research documents with the checking of data, interpreting them to get a deep understanding, obtaining the meaning contained, and scientific development in research. Main Findings: The implementation of the productive zakat program carried out by zakat institutions in Indonesia can reduce poverty. Almost all the funds' distribution programs carried out by zakat institutions run smoothly and have been proven to reduce poverty. The recipients of zakat who participated in the productive zakat program also showed an increment in their welfare. Applications: Zakat institutions in Indonesia can adopt productive zakat programs to reduce poverty. Besides, zakat institutions can increase their role in improving the welfare of the poor. On the other hand, the role of empowerment, primarily through the productive zakat program, can be applied in all zakat institutions in Indonesia. Novelty/Originality: The productive zakat program can be used as a model by the government as a means to improve the welfare of the community. Furthermore, the role of the zakat institution as a representative of the implementation of social care will increasingly be felt by the community, especially the needy recipients of zakat.